2002
DOI: 10.1152/ajplung.00329.2001
|View full text |Cite
|
Sign up to set email alerts
|

Histamine stimulates phosphorylation of adherens junction proteins and alters their link to vimentin

Abstract: Histamine increases microvascular permeability by creating small transitory (100-400 nm) gaps between adjacent endothelial cells at sites of vascular endothelial (VE)-cadherin-based adhesion. We examined the effects of histamine on the proteins within the VE-cadherin-based adherens junction in primary human umbilical vein endothelial cells. VE-cadherin is linked not only by beta- and alpha-catenin to cortical actin but also by gamma-catenin to the intermediate filament vimentin. In mature human umbilical vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 38 publications
2
73
1
1
Order By: Relevance
“…Tyrosine phosphorylation of VE-cadherin has been described in cells stimulated by several agents such as VEGF, thrombin, histamine, PAF and it was correlated with a rapid dissociation of adherens junctions, a critical step in angiogenesis and in inflammatory processes Zhao and Davis, 1998;Calcerrada et al, 2002;Shasby et al, 2002;Hudry-Clergeon et al, 2005). Yet, the specific tyrosine kinases involved in this process and the target sites of phosphorylation were still elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine phosphorylation of VE-cadherin has been described in cells stimulated by several agents such as VEGF, thrombin, histamine, PAF and it was correlated with a rapid dissociation of adherens junctions, a critical step in angiogenesis and in inflammatory processes Zhao and Davis, 1998;Calcerrada et al, 2002;Shasby et al, 2002;Hudry-Clergeon et al, 2005). Yet, the specific tyrosine kinases involved in this process and the target sites of phosphorylation were still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cytoplasmic domain of VE-cadherin contains nine tyrosine that represent potential target sites for tyrosine kinases. Indeed, VE-cadherin tyrosine phosphorylation has been reported in endothelial cells under several conditions including stimulation by VEGF Zhao and Davis, 1998;Shasby et al, 2002;Su et al, 2002). We recently reported that plateletactivating factor (PAF) increased VE-cadherin tyrosine phosphorylation in mouse endothelial cells and its association with the phosphatidylinositol 3 0 -(PtdIns3 0 )-kinase (Hudry-Clergeon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Vimentin and keratin are the major intermediate filament proteins in endothelial cells. Endothelial barrierdisrupting agents such as histamine induce vimentin phosphorylation in HUVEC, and cause its dissociation from adhesive complexes (18). Vimentin has also been shown to regulate focal adhesions in a bone marrow endothelial cell line (23).…”
mentioning
confidence: 99%
“…Fourth, previous studies indicated that histamine acutely increases transepithelial electrical conductance (G t ) in airway epithelia (19,22). In endothelia and cell lines, activation of histamine receptors disrupts the interaction of vascular endothelial-cadherin with the vimentin cytoskeleton to increase paracellular conductance (G p ) (23). Those studies focused on histamine's effect on adherens junctions, but whether tight junction function is also altered was not addressed.…”
mentioning
confidence: 99%